Stres Kerja Ditinjau dari Konflik Peran Ganda, Kelelahan Emosional dan Dukungan Sosial serta Dampaknya terhadap Komitmen Organisasi pada Dinas Perhubungan Provinsi Sumatera Utara - Mutiara Ananda Armi; Bunga Aditi; Sopi Pentana (LPPM IAI Nasional Laa Roiba Bogor, 2023)
This research is based on performance problems, namely the level of work stress of employees at the North Sumatra Transportation Service Personnel Agency which is thought to be caused by multiple role conflicts, emotional exhaustion, social support which also has an impact on organizational commitment.The approach in this research is regarding work stress which has an impact on organizational commitment. The research method used is the associative analysis survey method, namely knowing the relationship between two or more variables being studied based on the actual situation.This research method also uses quantitative analysis techniques through path analysis (PathAnalysis) which is intended to determine the magnitude of Dual Role Conflict (X) with Job Stress (Y) and Organizational Commitment.(Z) either simultaneously or partially.The conclusion in this research is that Dual Role Conflict and Emotional Fatigue do not have a direct influence on Organizational Commitment at the North Sumatra Transportation Service. This means that the existence of Dual Role Conflict and Emotional Fatigue in the North Sumatra Transportation Service does not have a negative impact on Organizational Commitment. Employees still have multiple role conflicts and emotional exhaustion even though they are based on existing organizational commitment.